Rationality of ACE-Inhibitor Use in Hypertension Patients at Community Health Center Simpang IV Sipin in Jambi City, During 2023-2024 - Fayza Nurrahmi; Mara Imam Taufiq Siregar; Anggelia Puspasari; Indrianti Indrianti; Budi Justitia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Hypertension is a chronic disease with a high global prevalence and a major risk factor for cardiovascular complications. Angiotensin-Converting Enzyme Inhibitors (ACE-Is) are widely recommended as first-line antihypertensive therapy, making evaluation of their rational use essential to ensure treatment safety and effectiveness. This descriptive observational study employed a retrospective design using medical records of hypertensive outpatients at Puskesmas Simpang IV Sipin, Jambi, from January 2023 to December 2024. A total of 100 eligible patients were included. The evaluation assessed the appropriateness of indication, dosage, frequency, duration of therapy, and potential drug interactions based on World Health Organization (WHO) criteria and the JNC 8 guidelines. Most patients were aged 60 years or older and were diagnosed with essential hypertension or hypertensive heart disease. All ACE-I prescriptions were appropriate for their clinical indications (100%), while dosage, frequency, and treatment duration fully complied with guideline recommendations. Most identified drug interactions were synergistic, whereas antagonistic (11%) and potentiation (25%) interactions were generally mild to moderate and clinically manageable. Overall, ACE-I prescribing was considered rational. Continuous monitoring remains important, particularly for patients at risk of clinically significant drug interactions to optimize therapeutic outcomes and patient safety.